East Asian Arch Psychiatry 2019
DOI: 10.12809/eaap1813
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Literacy in Cancer Outpatients in Singapore

Abstract: Objective: We aimed to evaluate the prevalence of depressive and anxiety symptoms and mental health literacy (MHL) in outpatients with or without cancer in Singapore. Methods: Oncology outpatients and outpatients without cancer (controls) were assessed for severity of anxiety and depressive symptoms (using the Hospital Anxiety and Depression Scale) and MHL regarding major depressive disorder and generalised anxiety disorder in terms of diagnosis, aetiology, treatment, and attitudes toward mental health service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The results found that higher position, higher professional credentials, higher hospital hierarchy, other specialist hospital, psychiatric hospital and unmarried status were positive predictors of MHL. The results were in accordance with previous studies (Poon et al, 2019;Hao et al, 2020).…”
Section: Level and Characters Of Mental Health Literacy Among Nursessupporting
confidence: 93%
“…The results found that higher position, higher professional credentials, higher hospital hierarchy, other specialist hospital, psychiatric hospital and unmarried status were positive predictors of MHL. The results were in accordance with previous studies (Poon et al, 2019;Hao et al, 2020).…”
Section: Level and Characters Of Mental Health Literacy Among Nursessupporting
confidence: 93%
“…Stage of cancer (Stage III and above), age (older‐aged), gender (female), and treatment (chemotherapy) were all significant indicators of psychological distress. Such findings have also been reported by other researchers from SEA region, although with smaller sample sizes (<250 participants) than the studies evaluated in the present review: Malaysia (Chen et al, 2019 ; Edib et al, 2016 ; Hassan et al, 2015 ; Isa et al, 2013 ; Leong Abdullah et al, 2015 ; Pahlevan Sharif, 2017 ; Priscilla et al, 2011 ; Saniah & Zainal, 2010 ; Wong & Lua, 2012 ; Yusof et al, 2016 ; Zainal et al, 2013 ), Philippines (Ledesma et al, 2011 ), Thailand (Cheung et al, 2015 ; Maneeton et al, 2014 ; Phuakpoolpol et al, 2018 ), Indonesia (Endarti et al, 2015 ; Haryani et al, 2018 ; Iskandarsyah et al, 2014 ; Vistad et al, 2011 ), Singapore (Chan et al, 2018 ; Cheng et al, 2014 ; Lim et al, 2014 and 2018; Liu et al, 2017 ; Mahendran et al, 2016 ; Peh et al, 2017 ; Poon et al, 2019 ; Teo et al, 2020 ), Cambodia and Myanmar (Pengpid & Peltzer, 2017 ), and Vietnam (Khue et al, 2019 ; Nguyen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed with cancer patients in 2019, the severity of depression and anxiety symptoms in people with and without a history of cancer was investigated, and MHL levels were evaluated in terms of major depressive disorder and generalized anxiety disorder. In this study, patients with cancer had lower MHL levels than healthy controls, and it was not associated with anxiety and depression symptoms 24 . Similarly, Pehlivan et al 15 did not determine a significant difference between university students with and without a diagnosis of psychiatric illness in terms of MHL.…”
Section: Discussionmentioning
confidence: 45%
“…Studies have concluded that high education level positively affects MHL 20,23,24 . On the other hand, Piper et al 22 did not find a relationship between education level and MHL in the elderly people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation